Quantitative structure-activity relationship of curcumin and its derivatives as μ-class of GST inhibitors - Enade Perdana Istyastono; Sudibyo Martono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
The Quantitative Structure-Activity Relationship (QSAR) study has been performed on curcumin and its derivatives as μ-class glutathione Stransferase inhibitors using atomic net charges as the predictors. The charges were resulted by semiempirical AM1 quantum-chemical calculations using the computational chemistry approach. The inhibition activity was expressed as the concentration that gave 50% inhibition of μ-class GST activity (IC50). The selection of the best QSAR equation models was determined by multiple linear regression analysis. Curcumin and its derivatives were reported as selective μ-class GST inhibitors. The enzyme plays an important role in the process of inflammation and the effectivity of anti lung-cancer compounds. μ-Class GST inhibitors could enhance the effectivity of anti lung-cancer compounds.The result showed that the best QSAR equation model of curcumin and its derivatives as μ-class GST inhibitors was described by.: log (1/IC50) = (-454.686) + (314.235)qC2 + (1593.499)qC3 + (452.563)qC4 + (1057.194)qC5 + (-1.756)qBenzene’ The equation was significant at 95% level with statistical parameters : n = 10, m = 5, F/FTabel = 3.335, R2 = 0.963, SE = 0.150, and PRESS = 0.559.Key words : QSAR analysis, curcumin, μ-class glutathione S-transferase, atomic net charge.